Novel biomarkers in patients with chronic kidney disease: an analysis of patients enrolled in the GCKD-study - Mirna, Moritz; Topf, Albert; Wernly, Bernhard; Rezar, Richard; Paar, Vera; Jung, Christian; Salmhofer, Hermann; Kopp, Kristen; Hoppe, Uta C.; Schulze, Paul Christian; Kretzschmar, Daniel; Schneider, Markus P.; et al. (Journal of Clinical Medicine, 2020)
Background: Chronic kidney disease (CKD) and cardiovascular diseases (CVD) often occur concomitantly, and CKD is a major risk factor for cardiovascular mortality. Since some of the most commonly used biomarkers in CVD are permanently elevated in patients with CKD, novel biomarkers are warranted for clinical practice. Methods: Plasma concentrations of five cardiovascular biomarkers (soluble suppression of tumorigenicity (sST2), growth differentiation factor 15 (GDF-15), heart-type fatty acid-binding protein (H-FABP), insulin-like growth factor-binding protein 2 (IGF-BP2), and soluble urokinase plasminogen activator receptor) were analyzed by means of enzyme-linked immunosorbent assay (ELISA) in 219 patients with CKD enrolled in the German Chronic Kidney Disease (GCKD) study. Results: Except for sST2, all of the investigated biomarkers were significantly elevated in patients with CKD (2.0- to 4.4-fold increase in advanced CKD (estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m² body surface area (BSA)) and showed a significant inverse correlation with eGFR. Moreover, all but H-FABP and sST2 were additionally elevated in patients with micro- and macro-albuminuria. Conclusions: Based on our findings, sST2 appears to be the biomarker whose diagnostic performance is least affected by decreased renal function, thus suggesting potential viability in the management of patients with CVD and concomitant CKD. The predictive potential of sST2 remains to be proven in endpoint studies.
Gesehen am 15.05.2020